Higher Genetic Diversity of the Common Sea Cucumber Holothuria (Halodeima) atra in Marine Protected Areas of the Central and Southern Ryukyu Islands - Hamamoto, Kohei; Soliman, Taha; Poliseno, Angelo; Fernandez-Silva, Iria; Reimer, James Davis (Frontiers in Conservation Science, 2021)
Recently, sea cucumbers (Echinodermata: Holothuroidea) have been over-exploited in many areas of the world, including in the Ryukyu Islands, southern Japan, due to increases in their economic importance. Nevertheless, management and protection of sea cucumbers are insufficient worldwide. The black sea cucumber Holothuria (Halodeima) atra Jaeger, 1833, inhabits a large range across the Indo-West Pacific Ocean and is a widely harvested species. Here we conducted population genetic analyses on H. atra using partial mitochondrial DNA sequences of cytochrome c oxidase subunit I (COI) and 16S ribosomal RNA (16S) to examine 11 different populations around three island groups in the middle Ryukyus; Okinawajima Island, the Kerama Islands, and the Sakishima Islands, all within Okinawa Prefecture. We found 27 haplotypes for COI and 16 haplotypes for 16S. Locations within national and quasi-national parks (Zamami Island, Keramas, and Manza, Okinawajima; managed by the national Ministry of Environment and Okinawa Prefecture, respectively) had the highest number of haplotypes, whereas locations with less management and more anthropogenic pressure had lower numbers The mean of all samples’ genetic diversity indices was moderate with regards to both haplotype and nucleotide diversity. According to our results, Zamami Ama was the most genetically diverse location based on both markers used, likely because it is located within Kerama-Shoto National Park with comparatively stricter regulations than most other locations. Based on our COI sequences, three-quarters of the locations with the highest haplotype diversity were found to be distant from Okinawajima Island, indicating that the genetic diversity of H. atra was reduced around Okinawajima Island. Our results possibly reflect negative impacts from anthropogenic pressures such as over-harvesting and coastal development, although future comprehensive research including sequences of nuclear loci is needed to confirm this hypothesis.